Specialist service for the provision of opthalmic benefit (circular) - Harwood, E. G.
1929-01 1929 1920s 8 pages APPENDIX A. SPECIALIST SERVICE FOR THE ADMINISTRATION OF OPHTHALMIC BENEFIT. The basis of the scheme is the provision of a specialist service as recommended in the Majority Report of the Royal Commission on National Health Insurance, and by implication in the Majority Report of the recent Committee on the Optical Practitioners' Bill, the specialist service being the dual one of ophthalmic surgeons and dispensing opticians. Ophthalmic treatment centres are available in the towns given in the Service List for the provision by qualified ophthalmic surgeons of ophthalmic examination, advice and a prescription for glasses where necessary, and for such operative treatment as can be given at a single consultation, together with a report where necessary for the guidance of the medical practitioner in attendance. Attached to each Treatment Centre are one or more qualified dispensing opticians who provide the lenses prescribed by the ophthalmic surgeon, together with the required frame, on the terms set out in the schedule hereunder. Each Centre is under the personal supervision of an ophthalmic surgeon. It should be understood that the great majority of cases are dealt with by ophthalmic surgeons at their private consulting rooms. Independent treatment centres will only be established in very densely populated areas for the convenience of the patient, and in all these cases the alternative of treatment at an ophthalmic surgeon's private consulting rooms at stated hours will be given. It will be appreciated that the scheme in its initial stages does not attempt to provide a universal service. The chain of treatment centres, though capable of infinite expansion, is intended primarily to illustrate the advantages of the service. It may be confidently stated, however, that, given the support of the Approved Societies, it will be possible to provide a complete service within twelve months from the initiation of the scheme. The Board will make the necessary arrangements for a suitable service in those towns in which there is at present no oculist. In those areas in which there exists an alternative supply of oculists, the attendance at sessions and at outlying towns will be a matter for arrangement between the oculists in that area, subject to the approval of the Medical Committee and the Board. The Treatment Centres are divided into two categories :— (1) Permanent establishments, known as "Central Clinics" ; (2) Centres operated from the ophthalmic surgeon's private consulting rooms at fixed hours. It should be noted that for the benefit of those members who may still desire to consult an ophthalmic surgeon privately at times other than those set aside for patients under this scheme, the existing arrangements whereby certain ophthalmologists see insured persons at a fee of a guinea will be continued, half the fee being met by the Approved Society and the other half by the member, or alternatively by the Approved Society direct ; the prescription in these cases will be dealt with by the Board's dispensing optician under the schedule set out hereunder. The central clinics are staffed by one or more oculists working on different days and evenings as local conditions demand. They are located in suitable premises conveniently situated and are fitted with the most modern equipment. It is the policy of the Board to make these centres a model of efficiency and every effort will be made to ensure the comfort and convenience of the patient. Ophthalmic surgeons attending these centres are paid a fee of 10s. 6d. per patient. The dispensing optician is in attendance to measure the patient and to dispense the glasses prescribed. He also carries out the routine work of the Centre so far as the reception of the patient and the completion of the forms is concerned. In the second category patients are seen by the oculist at his private consulting rooms at certain fixed hours at a fee of 10s. 6d. per patient. The dispensing optician is in attendance either on the premises, or, where this is not convenient to the oculist, in adjacent premises. 4 292/841.4/1/58